Urgensi Pelatihan Bela Negara bagi Warga Perbatasan Indonesia - Timor Leste guna Meningkatkan Jiwa Nasionalisme - Yahya, Yudhi; Widjayanto, Joni; Hendra, Afrizal (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The border region between Indonesia and Timor Leste possesses unique characteristics that render it susceptible to various threats. These threats are not limited to the military sphere but also encompass non-military aspects such as radicalism and foreign cultural influences. One approach to mitigating these threats is through national defense training. National defense is the foundation of a robust national defense system. The objective of this research is to analyze the urgency of national defense training for residents of the Indonesia-Timor Leste border region with the aim of enhancing their sense of nationalism. The researcher employed a qualitative research method. The results of this study indicate that national defense training in the Indonesia-Timor Leste border region has specific goals directed at strengthening the border residents' awareness of national sovereignty and simultaneously improving their capabilities in confronting various challenges. The recommendations proposed by the researcher to address the challenges of implementing national defense training in the Indonesia-Timor Leste border region include: improving infrastructure, adopting a holistic approach, enhancing inter-agency coordination, conducting intensive socialization, utilizing technology, and increasing the capacity of human resources..